Pengaruh Brand Equity, Kualitas Jasa dan Promosi Terhadap Minat Konsumen : Studi Kasus pada PT Amir Hassan Medan - Denni Denni; Leony Hoki; Vinna Vinna (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The research conducted aims to determine the effect of Brand Equity, service quality and promotion on consumer interest at PT. Amir Hassan Medan. This research is a quantitative descriptive study. The researcher distributed questionnaires to 75 respondents who are consumers of PT. Amir Hassan Medan. The data analysis techniques used are validity and reliability tests, classical assumption tests, multiple regression analysis, hypothesis testing through t and F tests, and determination coefficient tests (R2). From the results of the study, it is known that the Brand Equity Variable (X1) has a significant effect on the Consumer Interest variable (Y). The Service Quality Variable (X2) has a significant effect on the Consumer Interest variable (Y). The Promotion Variable (X3) has a significant effect on the Consumer Interest variable (Y). From the simultaneous F test, there is a significant influence between Brand Equity, Service Quality and Promotion on Consumer Interest at PT. Amir Hassan Medan. The influence of the three variables reaches 87.7% in influencing consumer interest. The remaining 12.3% is influenced by other factors not discussed in this study.